GAMBARAN KESEJAHTERAAN PSIKOLOGIS ORANG TUA DARI ANAK DENGAN KANKER YANG MENDAPAT KEMOTERAPI - Pradnya Paramita, Sang Ayu Amelia; Utami, Kadek Cahya; Manangkot, Meril Valentine (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022DO - 10.24843/coping.2022.v10.i03.p14, 2022)
Cancer becomes leading cause of death in children and adolescents. The most effective treatment for cancer in children is chemotherapy. Parents have an important role in child care so the good psychological well-being is needed in order to achieve success in treatment. This study aimed to describe the parents psychological well-being of children with cancer who got chemotherapy. This type of research was descriptive quantitative with a cross sectional method design. The sample was selected using a purposive sampling technique from parents in Yayasan Peduli Kanker Anak Bali, totaling 30 people. Based on the results of the study, it was found that the average age of parents was 35.40 years, the percentage of gender between men and women was equal to 50%, namely 15 people, the majority were at the high school education level, and the average psychological well-being of parents was in the low category.